Application of acceptance and commitment therapy (ACT) in inapetente conduct: a case study - Kevin Egúsquiza Vásquez (Interacciones)
In this article a case study on the loss of appetite approached from the Acceptance and Commitment Therapy is presented. First, experiential avoidance was conceptualized as a transdiagnostic dimension common to various human problems. Then, the story of the participant was reviewed and the assessment of the case was done by the Parental Acceptance and Action Questionnaire (PAAQ) and a record length of conduct, based on all functional analysis of the case was conducted. Subsequently, Acceptance and Commitment Therapy (ACT) was applied in order to break the avoidant repertoire and route the path of life towards the valued actions, after that three follow-ups were conducted. Finally, the results obtained from topographic and functional successful benefits were analyzed and discussed, contingent on the application of ACT in the field of eating behavior problems.